MO251HIGHLY SENSITIVE FLOW CYTOMETRIC DETECTION OF RESIDUAL B-CELLS AFTER RITUXIMAB IN ANTI-NEUTROPHIL CYTOPLASMIC ANTIBODY-ASSOCIATED VASCULITIS PATIENTS*. (29th May 2021) - Teng, Y K O; Van Dam, L; Oskam, Jelle; Kamerling, S W A; Arends, E J; Bredewold, Edwin; Berkowska@lumc.nl, M A; Van Dongen, J J M; Rabelink, T J; Van Kooten, Cees
Abstract: Background and Aims: B-cell depletion with rituximab (RTX) is an effective treatment for anti-neutrophil cytoplasmic antibodies (ANCA)-associated vasculitis (AAV) patients. Nevertheless, relapses are frequent after RTX, often preceded by B-cell repopulation suggesting that residual autoreactive B-cells persist despite therapy. Therefore, this study aimed to identify minimal residual autoimmunity (MRA) in the B-cell compartment of AAV patients treated with RTX. Method: EuroFlow-based highly-sensitive flow cytometry (HSFC) was employed to study B-cell and plasma cell (PC) subsets in-depth in AAV patients before and after RTX treatment. Additionally, peripheral blood mononuclear cells (PBMCs) of these RTX-treated AAV patients were cultured and  in vitro  stimulated with CpG, IL-2, and IL-21 to induce antibody-secreting cells (ASC). (ANCA)-IgG was measured in these supernatants by ELISA. Results: By employing EuroFlow-based HSFC, we detected circulating CD19 +  B-cells at all timepoints after RTX treatment, in contrast to conventional low-sensitive flow cytometry. Pre-germinal center (Pre-GC) B-cells, memory B-cells and CD20 + CD138 −  plasmablasts (PBs) were rapidly and strongly reduced, while CD20 − CD138 −  PrePC and CD20 - CD138 +  mature (m)PCs were reduced slower and remained detectable. Both memory B-cells and CD20 −  PCs remained detectable after RTX. Serum ANCA-IgG decreased significantly upon RTX. Changes in ANCA levels strongly correlated with changes in naive, switched CD27 +  and CD27 −  (double-negative) memory B-cells, but not with plasma cells. Lastly, we demonstrated  in vitro  ANCA production by AAV PBMCs, 24 and 48 weeks after RTX treatment reflecting MRA in the memory compartment of AAV patients. Conclusion: We demonstrated that RTX induced strong reductions in circulating B-cells, but never resulted in complete B-cell depletion. Despite strongly reduced B-cell numbers after RTX, ANCA-specific memory B-cells were still detectable in AAV patients. Thus, MRA is identifiable in AAV and can provide a potential novel approach in personalizing RTX treatment in AAV patients.